2019
DOI: 10.1111/and.13314
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐lipoic acid minimises reactive oxygen species‐induced damages during sperm processing

Abstract: Shearing forces during sperm preparation for assisted reproduction techniques may lead to excessive production of reactive oxygen species (ROS) which may have an unpleasant effect on embryonic development. In the current study, we assessed the effect of alpha‐lipoic acid (ALA) on ROS‐induced damages during sperm preparation process. Semen samples were collected from 15 normozoospermic men. Each semen sample was divided into two parts; one part was washed and centrifuged with sperm washing medium plus 0.02 mM A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Furthermore, the combination therapy maintained the membrane lipid ratio and reduced oxidative stress level. 13 Another study showed an antioxidant complex, containing the Comparing to other antioxidants, ALA showed stronger antioxidative activities, owing to its lipid-and water-soluble characteristics 15 and the ability to regenerate vitamins C and E. 16 We were interested in whether ALA as a sole antioxidant can increase the efficacy of NB-UVB in vitiligo. In our previous study, we evaluated the triple-combination treatment with ALA, NB-UVB and betamethasone injection on progressive nonsegmental vitiligo patients.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the combination therapy maintained the membrane lipid ratio and reduced oxidative stress level. 13 Another study showed an antioxidant complex, containing the Comparing to other antioxidants, ALA showed stronger antioxidative activities, owing to its lipid-and water-soluble characteristics 15 and the ability to regenerate vitamins C and E. 16 We were interested in whether ALA as a sole antioxidant can increase the efficacy of NB-UVB in vitiligo. In our previous study, we evaluated the triple-combination treatment with ALA, NB-UVB and betamethasone injection on progressive nonsegmental vitiligo patients.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, unbalanced in oxidant/antioxidant status with the increase formation of LPO (35) associated with destruction of sperm plasma membrane, losing integrity of mitochondrial membrane and sperm DNA damage leading to infertility (34). Co-treatment of lead with ALA shows a significant improvement in sperm parameters may be due the potential antioxidant properties of ALA through its ability to scavenge FRs in aqueous and non-aqueous phases (36) and its ability to synthesized robust shield surrounding the sperm cell membrane (23). In our study, histopathological alterations in lead treated rats characterized with degenerative changes was observed in lead acetate treated rats due to negatively effects on male reproductive system.…”
Section: Discussionmentioning
confidence: 99%
“…Also, alpha-lipoic acid, an organo-sulphur compound derived from octanoic acid, is regarded as a universal antioxidant as it acts as a cofactor for many enzymes and is shown to restore endogenous antioxidants such as oxidised vitamin Cand E, thereby protecting organelles, cells and tissue from the damaging effects of excessive ROS production (Taherian et al, 2019). Moringa oleifera leaves are also rich in vitamin C and E (Ajantha et al, 2018), which have been indicated as major chain-breaking antioxidants with strong reducing potential that attenuate free radical generating reactions (Brash & Havre, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Data were represented as mean ± SEMof 200 spermatozoa from 34 healthy donors their involvement in male fertility regulation are highly dependent on cofactors such as Zn, Se, Mg, Mn, Fe 3+ and Cu (Dobrakowski et al, 2018) whose presence in MO leaves has been validated (Dilawar et al, 2018). Centrifugation during the processing of semen increases the generation of ROS results in a loss in sperm motility and viability and induces DNA damage in spermatozoa (Henkel et al, 2012;Taherian et al, 2019). Semen samples obtained from normozoospermic men, washed and centrifuged with sperm washing media, in the presence of alpha-lipoic acid (0.02 mM) maintained sperm viability, and motility through the reduction of ROS production as well as prevention DNA damage (Taherian et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation